Energy and macronutrient intake and risk of differentiated thyroid carcinoma in the European Prospective Investigation into Cancer and Nutrition study. Issue 1 (30th July 2015) - Zamora‐Ros, Raul; Rinaldi, Sabina; Tsilidis, Konstantinos K.; Weiderpass, Elisabete; Boutron‐Ruault, Marie‐Christine; Rostgaard‐Hansen, Agnetha Linn; Tjønneland, Anne; Clavel‐Chapelon, Françoise; Mesrine, Sylvie; Katzke, Verena A.; Kühn, Tilman; Förster, Jana; et al.
<x xml:space="preserve">Abstract</x> Incidence rates of differentiated thyroid carcinoma (TC) have increased in many countries. Adiposity and dietary risk factors may play a role, but little is known on the influence of energy intake and macronutrient composition. The aim of this study was to investigate the associations between TC and the intake of energy, macronutrients, glycemic index (GI) and glycemic load in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. The study included 477, 274 middle‐age participants (70.2% women) from ten European countries. Dietary data were collected using country‐specific validated dietary questionnaires. Total carbohydrates, proteins, fats, saturated, monounsaturated and polyunsaturated fats (PUFA), starch, sugar, and fiber were computed as g/1, 000 kcal. Multivariable Cox regression was used to calculate multivariable adjusted hazard ratios (HR) and 95% confidence interval (CI) by intake quartile (Q). After a mean follow‐up time of 11 years, differentiated TC was diagnosed in 556 participants (90% women). Overall, we found significant associations only with total energy (HRQ4vs.Q1, 1.29; 95% CI, 1.00–1.68) and PUFA intakes (HRQ4vs.Q1, 0.74; 95% CI, 0.57–0.95). However, the associations with starch and sugar intake and GI were significantly heterogeneous across body mass index (BMI) groups, i.e., positive associations with starch and GI were found in participants with a BMI ≥ 25 and with sugar intake in those with BMI < 25. Moreover, inverse associations with starch and GI were observed in subjects with BMI < 25. In conclusion, our results suggest that high total energy and low PUFA intakes may increase the risk of differentiated TC. Positive associations with starch intake and GI in participants with BMI ≥ 25 suggest that those persons may have a greater insulin response to high starch intake and GI than lean people.